Effects of a single omitted milking on one udder quarter in high cell count dairy cows in an AMR system with or without re-sorting for a second milking - Lidholm, Lovisa (SLU/Dept. of Animal Nutrition and Management (until 231231), 2016)
The milk production is developing towards fewer but larger herds with automatic milking systems. The most recent system for milking that has been developed for managing milking in large herds is an automatic milking rotary (AMR), which was launched in 2010. Although several benefits with automated systems have been reported there is an increased risk for incomplete or omitted milking due to attachment failure or that the cow kicks off one or more teat cups after attachment. An incomplete milking of one or more udder quarters can lead to reduced milk yield, a lower quality of milk and milk leakage, which may lead to decreased udder health. Therefore, cows who are incompletely milked in an AMR are resorted to a second milking after the first milking occasion, but this resorting reduces the efficiency of the AMR and affects the cows' time budget. Somatic cell count (SCC) is the most common indicator for udder health and subclinical mastitis, increases in SCC is an important part of the cow's immune system. In Sweden, SCC above 200 000 cells / ml milk is classified as high cells in the milk and the cow probably has mastitis in one or more udder quarters. SCC can vary depending on various factors, such as stage of lactation and milk fraction. There is also a day to day variation in SCC and this is higher for cows with mastitis than for healthy cows. The aim of the study was to evaluate if cows with a milk SCC above 200 000 cells/ml that have passed peak lactation really need to be re-milked after a single incomplete milking in an AMR. 16 cows were included in the study, on the morning day four of the experiment, half of them were re-sorted into a second milking after the first milking occasion - to be milked on the fourth udder quarter. The remaining seven cows were not re-sorted after the first milking and therefore they were not milked on the fourth udder quarter this morning. The udder quarter with the highest SCC was selected to the treatment from all cows. Milk samples were taken daily and were analyzed for SCC, milk composition and milk yield during three days before the treatment to ten days after the treatment. The results showed no significant effect on either the SCC, milk composition or milk yield due to the omitted milking, there were also no significant differences between the re-sorted group and the group that was not re-sorted. The study did not show any negative effects on SCC, milk composition or milk yield by an omitted milking on one udder quarter for cows with high SCC. However, the study needs to be repeated since the low number of cows included in the study allows limited conclusions of the data. Further study should have a higher number of cows to clarify if the results in this study are reliable.